The Effect of Mental Training That Accompanies Skill Learning to Learn Some of Fundamental Skills in Boxing - Jalal, Kamal (Journal of Physical Education, 2009)
The study purpose: This study is aimed at knowing the effect of mental training that accompanies skill learning, and comparing it with a skillful learning program to learn some of the Fundamental Skill of Boxing. The study results: Results indicated that there wan no significant difference between the pre and posttest of imagination for the control group. There was a significant difference between the pre and posttest of imagination for the experimental group. There was a significant difference between the control and experimental groups in the skill test and favor of the second group too. These results emphasized the importance of the mental training that accompanies skill learning relative to skill learning alone